Servicios gastronómicos para el mejoramiento de la atención al cliente en el sector Los Cerritos cantón Quinsaloma en el año 2019 - Santos Hernandez, Luis Miguel (2020)
Gastronomic tourism is a growing trend, year after year tourists move from their place of residence, in search of new culinary experiences, with different and exotic products, visiting gastronomic festivals, markets in search of fresh products or visiting restaurants, to delight Your palate with local cuisine. Tourism activity is currently characterized by major changes motivated by the need to adapt to an increasingly demanding and active demand. Thus, and among other changes, we find that travelers tend to make more trips throughout the year, although shorter, are more informed of both the destination and the product or are looking for new types of tourist resources. As a result of all these changes, a thematic tourism appears, among which the issues related to the recovery of the cultural and social heritage of the geographical areas, the contact with nature and the knowledge of the customs of the local community itself stand out. Tourism today has given a radical change the tourist seeks new sensations a way to be more involved with the culture of each town is so that gastronomy is presented as a worthy representative of the ancestral traditions its way of being cooked, complies with the The demands of those who wish to enjoy this tourist part of Latin America have enormous potential to be exploited where each country stands out for its culinary arts very different from the others.